Cold-stored whole blood platelet function is preserved in injured children with hemorrhagic shock. Issue 1 (July 2019) - Leeper, Christine M.; Yazer, Mark H.; Cladis, Franklyn P.; Saladino, Richard; Triulzi, Darrell J.; Gaines, Barbara A.
Abstract : BACKGROUND: Recent data demonstrate the safety of uncrossmatched cold-stored whole blood (WB) transfusion in pediatric trauma patients. The hemostatic capabilities of platelets within the cold-stored WB unit have been demonstrated via in vitro studies and animal models. However, platelet function has not been evaluated in pediatric recipients of cold-stored WB transfusions. METHODS: Injured children, 2 years or older and 10 kg or greater with hemorrhagic shock received up to 30 mL/kg of cold-stored, low titer (<50) anti-A and -B, leukoreduced, group O- WB during their initial resuscitation. Patients were included if (1) they received WB and no conventional platelets, and (2) platelet count and thromboelastography maximum amplitude were measured both before and after transfusion. These data and relevant clinical outcomes (mortality, intensive care unit length of stay [LOS], hospital LOS and ventilator days) were compared to a historical cohort of pediatric trauma patients who received uncrossmatched red blood cells (RBC) and conventional room temperature platelets. RESULTS: Twenty-two children were included in the study; 14 in the component cohort versus 8 in the WB cohort. Neither posttransfusion platelet count (129 × 109/L vs. 135 × 109/L) nor function (thromboelastography maximum amplitude, 59.5 mm vs. 60.2 mm) differed significantly between children receiving cold-stored platelets within the WB unit versus children who received conventional warm platelets. Median (interquartile range) weight-adjusted platelet transfusion volume in the historical cohort was 4.6 (2.5–7.7) mL/kg vs. 2.4 (1.3–4.0) mL/kg in the WB cohort ( p = 0.03). There was no difference between groups in age, race, mechanism of injury, Injury Severity Score, vital signs, and severe traumatic brain injury (TBI). Outcomes, including mortality, intensive care unit LOS, hospital LOS, and ventilator days, were not significantly different between groups. CONCLUSION: No difference was seen in posttransfusion platelet number or function in severely injured children receiving cold-stored WB platelets as compared to those receiving conventional room temperature-stored platelets. Larger cohorts are required to confirm these findings. LEVEL OF EVIDENCE: Therapeutic, level IV.